Improving Physical Fitness Learning Outcomes Through the Problem Based Learning (PBL) Model in Physical Education Learning for Grade IV of SDN 1 Landasan Ulin Selatan - Ansari, Ahmad; Fauzan, Lazuardy Akbar; Suadmaji, Suadmaji (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2026)
The low physical fitness learning outcomes of fourth-grade students of SD Negeri 1 Landasan Ulin Selatan, characterized by an average score of 70.5 and only 50.0% completion of 24 students, became the background of this study. Although the Problem Based Learning (PBL) model has been widely applied in PJOK learning, classroom action research that specifically examines the progressive integration between video-based motion modeling in the first cycle and competitive motion games in the second cycle as a strategy to improve physical fitness learning outcomes is still very limited. This study aims to improve physical fitness learning outcomes that include aspects of knowledge, skills, and attitudes through the application of PBL with a progressively differentiated two-cycle design. The type of research is Classroom Action Research (CAR) model Kemmis and McTaggart. The subjects of the study were 24 fourth-grade students selected based on their low initial learning outcomes. The instruments used included an attitude observation sheet (indicators: mutual cooperation, independence, critical reasoning, discipline; scale 1–4), a skills observation sheet (indicators: running on the spot, squats, and push-ups; scale 1–4), knowledge test questions (4 descriptive items), and a student reflection sheet. All instruments were validated by two validators. Quantitative data were analyzed using a comparative descriptive technique with the final score formula: knowledge (30%) + skills (60%) + attitudes (10%), then compared with the Benchmark Reference Guide (PAP). In Cycle I, PBL assisted by learning videos increased the average final score to 74.8 with 66.7% completion. In Cycle II, the integration of fitness movements in competitive movement games increased the average to 82.4 with 83.3% completion, exceeding the 75% success indicator. The findings indicate that PBL supported by video-based stimulation and competitive movement games contributed to the holistic improvement of students' physical fitness learning outcomes in the classroom context studied.